(untitled) (Iranian Journal of Kidney Diseases, 2019)
Introduction: Currently, conflicting evidence exists among community-based studies as to whether Chronic kidney disease (CKD) is a Cardiovascular (CVD) risk equivalent. We aimed to evaluate the effect of CKD on CVD based on large trial results. Methods: To perform a secondary analysis, we obtained the data of SPRINT trial from NHLBI Data Repository Center. 2646 subjects with baseline CKD and 6715 without CKD were enrolled. A composite of myocardial infarction, other acute coronary syndromes, stroke, heart failure, or death from cardiovascular causes was considered as primary outcome. Results: Throughout the 3.21 years of follow-up, presence of CKD, compared to those without CKD, negatively affected the primary outcome (incidence rate, 2.84% per year vs. 1.55% per year in patients with and without CKD, respectively; Hazard ratio, 1.83; 95% CI, 1.49 to 2.11; P<0.001). This finding was consistent across all the secondary outcomes. However, the risk was not as great as those with clinical cardiovascular disease (incidence rate, 4.13% per year). Presence of CKD was the strongest predictor of developing AKI with intensive blood pressure reduction, increasing its chance by 215%. Conclusions: SPRINT is the first trial revealing that CKD is an independent risk factor for CVD. However, CKD could not be considered as a CVD risk equivalent. In the presence of CKD, with intensive blood pressure reduction the chance of AKI is dramatically increased.